Incremental Forming of Tunnel Type Parts. (2017) - Afonso, Daniel; Sousa, Ricardo Alves de; Torcato, Ricardo
Abstract: Sheet metal incremental forming processes, as single point incremental forming (SPIF) have been more intensively studied since the beginning of the 2000's. Both academic benchmark parts and real application parts have been formed, studying job parameters, material formability, part quality, and evolving the process to an industry ready state. However, studies have been performed using full constrained sheets, held all around in a sheet holder and forming a container configuration part. Despite the possibility of extending the part surface to the blank sheet plane and post process cutting operations that allow achieve a more flexible range of part geometry, the container configuration often limits the part size and leads to significant waste of material. The aim of this study is to explore the formability of tunnel type parts using the purpose built SPIF machine at the University of Aveiro. The goal is to increase the flexibility of the process by fitting to a given geometry, increasing the maximum part size and reducing both the need of post processing operations and material waste. Conventional forming parameters are first used to validate the concept on simple geometries and factorial tests are then used to explore best suitable forming parameters for tunnel configuration parts, exploring both formability, accuracy and time efficiency. Experimental studies address not only to full tunnels but also to semi tunnel type parts, embracing a more flexible part geometry. The study finishes with the manufacture of some more elaborate geometries, testing and validating the tunnel incremental forming concept to be used in freeform parts.